Biphasic Effect of Buspirone on the H-Reflex in Acute Spinal Decerebrated Mice - Develle, Yann; Leblond, Hugues (Frontiers in Cellular Neuroscience, 2020)
Pharmacological treatment facilitating locomotor expression will also have some effects on reflex expression through the modulation of spinal circuitry. Buspirone, a partial serotonin receptor agonist (5-HT1A), was recently shown to facilitate and even trigger locomotor movements in mice after complete spinal lesion (Tx). Here, we studied its effect on the H-reflex after acute Tx in adult mice. To avoid possible impacts of anesthetics on H-reflex depression, experiments were performed after decerebration in un-anesthetized mice (N = 20). The H-reflex in plantar muscles of the hind paw was recorded after tibial nerve stimulation 2 h after Tx at the 8th thoracic vertebrae and was compared before and every 10 min after buspirone (8 mg/kg, i.p.) for 60 min (N = 8). Frequency-dependent depression (FDD) of the H-reflex was assessed before and 60 min after buspirone. Before buspirone, a stable H-reflex could be elicited in acute spinal mice and FDD of the H-reflex was observed at 5 and 10 Hz relative to 0.2 Hz, FDD was still present 60 min after buspirone. Early after buspirone, the H-reflex was significantly decreased to 69% of pre-treatment, it then increased significantly 30–60 min after treatment, reaching 170% 60 min after injection. This effect was not observed in a control group (saline, N = 5) and was blocked when a 5-HT1A antagonist (NAD-299) was administered with buspirone (N = 7). Altogether results suggest that the reported pro-locomotor effect of buspirone occurs at a time where there is a 5-HT1A receptors mediated reflex depression followed by a second phase marked by enhancement of reflex excitability.